Geospatial distribution of under-five mortality in Alexandria, Egypt: a cross-sectional survey - Samar Abd ElHafeez; Mahmoud A. Hassan; Esraa Abdellatif Hammouda; Abdelrahman Omran; Ola Fahmy Esmail; Amira Saad Mahboob; Mohamed Mostafa Tahoun; Dina Hussein El Malawany; Mohamed Kamal Eldwiki; Passent Ehab El-Meligy; Ehab Elrewany; Shaimaa Gadelkarim Ebrahim Ali; et al. (SpringerOpen, 2023)
Abstract Background Globally, infectious diseases, including pneumonia, diarrhea, and malaria, along with pre-term birth complications, birth asphyxia and trauma, and congenital anomalies remain the leading causes of death for under-five mortality (U5M). This study aimed to identify the geospatial pattern of U5M in Alexandria and its key determinants. Methodology We analyzed the geospatial distribution of 3064 deaths registered at 24 health offices reported from January 1, 2018 to June 30, 2019. We adopted two methods of analysis: geospatial analysis and the structural equation model (SEM). Result Neonates represented 58.7% of U5M, while post-neonates and children were 31.1%, 10.2%respectively. Male deaths were significantly higher compared to females (P = 0.036). The main leading causes of U5M were prematurity (28.32%), pneumonia (11.01%), cardiac arrest (10.57%), congenital malformation (9.95%), and childhood cardiovascular diseases (9.20%). The spatial distribution of U5M (including the most common three causes) tends to be clustered in western parts of Alexandria (El Hawaria, Bahig, Hamlis, and Ketaa Maryiut). SEM showed the total effects of exogenous and intermediate variables on U5M. The U5M proportionately increased by living in rural areas (8.48), followed by crowding rate (8.35), household size (1.36), population size (0.52), and illiteracy average (0.06). On the contrary, the U5M decreased with increasing access to sanitation (-0.17) and access to drinking water (-4.55). Conclusion Illiteracy, and poor locality characteristics (household size, population density, and access to water supply and sanitation) were statistically significant predictors of U5M.